Study of the epidemiological profile of the vaccination against HPV in the State of Piauí (Research, Society and Development, 2021)
Objective: To evaluate the epidemiological profile of vaccination against HPV in the state of Piauí. Methodology: The study of this work was through an exploratory, epidemiological and descriptive research with a transversal, quantitative and retrospective approach. The epidemiological data collected were related to the State of Piauí and the collection was carried out between Marchand April 2021, from the data base of the Information Technology Department of the Unified Health System (DATASUS). Data from individuals aged between 9 and 26 years old, female and male and Who received the quadrivalent vaccine against HPV between 2017 and 2020 were included. Results and Discussion: Males aged 11 years were those with the highest number of vaccinations (33.5%), while the 17-year-old group (0.1%) had the lowest number of vaccinations, the first dose was 53% in females and 61.9% in males, obtaining an application that in the second dose was 46.8% in females and 37% in males. Final considerations: In this way, it is clear that the state of Piauí did not obtain a significant and satisfactory demand for the HPV vaccine in the target period of this study. Although the Northeast region was the second region in the country that vaccinated the most against HPV, Piauí was not in a good position during this period, and consequently did not reach the target stipulated by the Ministry of  Health for each year.